Kontestasi Figural dalam Industri Budaya Yoga - Kadek Hemamalini (UHN IGB Sugriwa Denpasar, 2018)
Yoga became a popular culture can not be separated from the influence of cultural industries that then bring a new face in yoga practice. Yoga is known today is yoga asanas which besides beneficial to health is also full of entertainment nuance as an implication of postmodern society lifestyle and also the implications of the role of media in society. So it is said yoga practice is now a propan yoga practice, away from sacred values like the teachings that should be in yoga itself. This phenomenon raises the awareness of certain groups of people to show and restore the true teachings of yoga through yoga-yoga mass done in the areas of the shrine by taking time yoga as it should. So no doubt this condition raises social stratification that appears in the community in a form of contestation of yoga practices.